2013
DOI: 10.1080/15732479.2010.541265
|View full text |Cite
|
Sign up to set email alerts
|

The consistency of visual sewer inspection data

Abstract: International audienceIn common with most infrastructure systems, sewers are often inspected visually. Currently, the results from these inspections inform decisions for significant investments regarding sewer rehabilitation or replacement. In practice, the quality of the data and its analysis are not questioned although psychological research indicates that, as a consequence of the use of subjective analysis of the collected images, errors are inevitable. This article assesses the quality of the analysis of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 9 publications
(10 reference statements)
2
59
2
Order By: Relevance
“…As the impact on solids deposition was found to be more pronounced in the smaller diameter sewers in the upper parts of the sewer networks which are generally hard to access, the classification of separate deposits were in many cases based on subjective judgements from CCTV documentation. Dirksen et al (2013a) have reported that classification of structural deficiencies by CCTV-camera operators were found to be flawed, however, no study has to date assessed the veracity and uncertainty with regard to the reporting of in-sewer deposits.…”
Section: Visual Assessment Of Deposits and Condition In Sewersmentioning
confidence: 95%
“…As the impact on solids deposition was found to be more pronounced in the smaller diameter sewers in the upper parts of the sewer networks which are generally hard to access, the classification of separate deposits were in many cases based on subjective judgements from CCTV documentation. Dirksen et al (2013a) have reported that classification of structural deficiencies by CCTV-camera operators were found to be flawed, however, no study has to date assessed the veracity and uncertainty with regard to the reporting of in-sewer deposits.…”
Section: Visual Assessment Of Deposits and Condition In Sewersmentioning
confidence: 95%
“…As shown in Table 5, disagreements can be due to an inspector failing to recognise a defect (FN) and a defect being reported, although there is none (FP). Dirksen et al (2013) indicated for visual inspections in sewage infrastructure that the probability of FN is significantly larger that the probability of FP. In our case, FN was somewhat higher only for parameter A (Damage level).…”
Section: Discussion On the Use Of First-level Inspection Reports For mentioning
confidence: 99%
“…The cost of the majority of these methods prohibits their regular use in routine bridge condition assessment, executed for all bridge structures within network. Visual inspection is accompanied by condition assessment methodology that translates the identified damages and faults into a quantitative measure; condition rating coefficient, R, is, however, cost effective but less reliable [5,12,13] . The survey of inspection practices on network level, performed for various countries [14], nevertheless shows that worldwide, the majority of road network managing agencies use this method in their daily work.…”
Section: Bridge Condition Assessment Methodologymentioning
confidence: 99%